Exploring Educational Needs of Primary Education Directors in Administration Issues - Ζαχάρης Γεώργιος; Σουρλή Κατερίνα; Τσιαχρή Μαρία; Μωύσογλου Ιωάννης (Education Sciences, 2020)
The aim of the study was the educational needs investigation on administrational issues of the primary schools and kindergartens principals’ of Fthiotis County for the school year 2018-2019. One hundred in principals and deputy principals were included in the study. Totally 132 completed questionnaires were collected (86.27% participation rate). According to the participants, the most important fields regarding their educational needs were the change management and innovation implementation (53%), conflict management with students’ parents (53%) and the introduction of the new technology for pedagogical and administrational scope (52,3). The most important incentives for participation in the training programs emerged the skills improvement (84.1%) and the personal interesting for the scientific field (61.4%). According the results of the multivariate statistical analysis between the independent variables and the score of the educational needs, the participants without lesson during under graduate studies had greater need for training programs compared to those with administration lesson during under graduate studies (coefficient b = 0.29, 95% CI = 0.06 to 0.51, p = 0.013). The investigation of teachers' educational needs can contribute to the design appropriate training programs, that can provide the knowledge and skills, which are essential for the school unit management.